MARKETING CHARACTERISTICS OF INSURANCE MARKET IN UKRAINE - А. Sabirova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The current state of the insurance market of Ukraine in the post-crisis period, by comparison with the pre-crisis was investigated in the paper. The insurance market in the pre-crisis period grew rapidly, but was unable to withstand the economic crisis and suffered a crushing blow. The economic crisis of 2008-2009 led to a decrease of the demand for financial services in general and insurance services in particular. The lack of development of the insurance market created high barriers for responding and adapting to changes that occurred during the crisis.